2007
DOI: 10.1137/070684392
|View full text |Cite
|
Sign up to set email alerts
|

Error Estimation for Reduced‐Order Models of Dynamical Systems

Abstract: Abstract. The use of reduced order models to describe a dynamical system is pervasive in science and engineering. Often these models are used without an estimate of their error or range of validity. In this paper we consider dynamical systems and reduced models built using proper orthogonal decomposition. We show how to compute estimates and bounds for these errors, by a combination of small sample statistical condition estimation and error estimation using the adjoint method. Most importantly, the proposed ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…However, we demonstrated that this control law is energetically inefficient. These numerical results agree to a large extent to those obtained previously by other researchers [38,40,69] using the twodimensional Navier-Stokes equations to solve the optimal control problem. Compared with those studies, the main advantage of our approach is that it leads to a significant reduction of the numerical costs because the optimization process itself is completely based on reduced-order models only.…”
Section: Discussionsupporting
confidence: 89%
“…However, we demonstrated that this control law is energetically inefficient. These numerical results agree to a large extent to those obtained previously by other researchers [38,40,69] using the twodimensional Navier-Stokes equations to solve the optimal control problem. Compared with those studies, the main advantage of our approach is that it leads to a significant reduction of the numerical costs because the optimization process itself is completely based on reduced-order models only.…”
Section: Discussionsupporting
confidence: 89%
“…As expected, L2 error relative to a ground truth solution increases as the dynamics diverge from those of the training simulation. Characterizing the error of subspace simulations under arbitrary perturbations is an interesting and subtle topic [Homescu et al 2005], so we leave a more thorough analysis as future work.…”
Section: Implementation and Resultsmentioning
confidence: 99%
“…Such backups are not acceptable in offline animation, since they would require coupled simulators (fluids, rigid bodies) to be backed up as well, which would invalidate any performance gains. The dual weighted residual (DWR) method [Meyer and Matthies 2003] as well as the method of Homescu et al [2006] take a different approach and solve the adjoint of a known simulation result backwards in time to obtain a priori reduced-order error bounds on perturbed versions of the simulation. These two methods still bootstrap off of existing simulation data, so they cannot be applied to the case where the simulation is only computed once.…”
Section: Related Workmentioning
confidence: 99%
“…This estimate is conservative -subspace error is usually characterized as a sum of projection error and integration error (for example, see Homescu et al [2006]), with integration error being the only component that compounds over time. We pessimistically assume that all of the error is integration error.…”
Section: Estimating How Many Steps To Skipmentioning
confidence: 99%